2023
DOI: 10.1002/admi.202202205
|View full text |Cite
|
Sign up to set email alerts
|

Surface‐Dependent Electrocatalytic Activity of CoSe2 for Lithium Sulfur Battery

Abstract: Electrocatalysts play key roles in improving the performance of lithium sulfur (Li‐S) batteries. Here, the electrocatalytic activity of different CoSe2 surfaces for the polysulfide redox reactions in Li‐S batteries, by means of first‐principle calculations is considered. The authors demonstrate that there are obvious differences in surface energy (0.7–2.34 J m−2), adsorption energy for lithium polysulfides (LiPSs) (1.2–3.5 eV), Gibbs free energy of sulfur reduction reaction (SRR) (0.37–1.16 eV), and Li2S decom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 56 publications
1
2
0
Order By: Relevance
“…Our analysis reveals that the initial step involving the conversion of S 8 to Li 2 S 8 is exothermic on AMs, consistent with prior studies. , The Li 2 S 2 –Li 2 S is the rate-determining step in most Li–S battery studies, such as graphene, oxychloride . This applies to the Be-TiS 2 , but the rate-determining step is Li 2 S 4 –Li 2 S 2 in other M-TiS 2 and the pristine TiS 2 , which is consistent with calculations in other TMDs, such as NbS 2 and CoSe 2 . Furthermore, Zhao et al found that the difference between E ZPE and T Δ S was less than 0.05 and 0.1 eV, and the same E ZPE and T Δ S were used to shorten the calculations.…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…Our analysis reveals that the initial step involving the conversion of S 8 to Li 2 S 8 is exothermic on AMs, consistent with prior studies. , The Li 2 S 2 –Li 2 S is the rate-determining step in most Li–S battery studies, such as graphene, oxychloride . This applies to the Be-TiS 2 , but the rate-determining step is Li 2 S 4 –Li 2 S 2 in other M-TiS 2 and the pristine TiS 2 , which is consistent with calculations in other TMDs, such as NbS 2 and CoSe 2 . Furthermore, Zhao et al found that the difference between E ZPE and T Δ S was less than 0.05 and 0.1 eV, and the same E ZPE and T Δ S were used to shorten the calculations.…”
Section: Resultssupporting
confidence: 89%
“…12 This applies to the Be-TiS 2 , but the ratedetermining step is Li 2 S 4 −Li 2 S 2 in other M-TiS 2 and the pristine TiS 2 , which is consistent with calculations in other TMDs, such as NbS 2 55 and CoSe 2 . 56 Furthermore, Zhao et al 56 found that the difference between E ZPE and TΔS was less than 0.05 and 0.1 eV, and the same E ZPE and TΔS were used to shorten the calculations. It shows that the ΔE has an important effect on the Gibbs free energy.…”
Section: Resultsmentioning
confidence: 99%
“…[25][26][27][28] Furthermore, CoSe 2 can also reduce the nucleation barrier of Li 2 S and promote the uniform deposition of Li 2 S due to its excellent catalytic activity. [29][30][31][32] In particular, the CoSe 2 derived from ZIF-67 can provide abundant catalytic active sites for the conversion of LiPSs and contribute to the realization of high-sulfur loaded LSBs. [26,29,33] Unfortunately, such CoSe 2 electrocatalysts are anchored to a 3D porous carbon framework and composed of many discontinuous nanoparticles, which are easy to agglomerate or even break up during continuous charge and discharge process.…”
Section: Introductionmentioning
confidence: 99%